program in Photoshop Achieving the overall values ​​of the publications (Journal of the College of Basic Education, 2023)
Technological development and software, including graphic programs (Photoshop) and the Internet, have changedthe world of publications, many of its pillars have become developed and the human habits associated with themshe too began to change; The first signs of this movement began in the mid-nineties of the last century.With the advent of electronic text, online publishers, and online libraries.Digital libraries and publications are a visual means of communication that convey ideas to the recipient.